"A Hand of Ivory": Moving Objects in Psellos' Oration for his Daughter Styliane. A Case Study. (October 2021) - Pizzone, Aglae
This paper takes its cue from the recent interest in materiality and "things" in the field of Byzantine studies, to explore the role of objects in evoking being moved. First, it advances a new model to explain the relationship between being moved and affordances. Second, it focuses on a specific case study, that is Michael Psellos' funeral oration for his daughter Styliane (1054), who died of smallpox at the age of 9 years old. The paper sheds light on how affective affordances of an object contribute to the evocation of being moved in literary texts, working within and affecting narrative patterns. While building on the experience of ethical and spiritual principles clearly recognizable by the audience, such affordances point toward the activation of broader core values.